2014
DOI: 10.17503/agrivita-2014-36-1-p014-018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth and Yield Performance on Inoculated Chili Pepper Hybrids by Cucumber Mosaic Virus

Abstract: Tolerance cultivar is a best control measure to reduce losses due to virus attack in the field. Study on growth and yield of new cultivars compared to the commercial ones is an important step in cultivar development. The objective of this research was to evaluate growth and yield performance of inoculated new chilli pepper hybrids by Cucumber Mosaic Virus (CMV) compared to a commercial and similar fruit size one. Twelve new hybrids and one commercial hybrid cultivar 'Prada', as a control, were evaluated in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Observations at the age of 6 weeks after transplanting showed that all tested genotypes lessened in growth. Vegetative growth of chili pepper showed varied performance [13]. Saline stress decreased plant height by more than 50% in genotypes A03, A04, A07 A11 and A26.…”
Section: Performance Of Cayenne Genotypes On Nacl-stressed Mediamentioning
confidence: 99%
“…Observations at the age of 6 weeks after transplanting showed that all tested genotypes lessened in growth. Vegetative growth of chili pepper showed varied performance [13]. Saline stress decreased plant height by more than 50% in genotypes A03, A04, A07 A11 and A26.…”
Section: Performance Of Cayenne Genotypes On Nacl-stressed Mediamentioning
confidence: 99%
“…Meanwhile, for Tanjung, only fruit length and weight per fruit were greater than the average of all varieties, while the remaining attributes were lower (< 1). According to Herison et al (2014), chili fruit length is defined by genetics. Basuki et al (2014) stated that even though the consumer's demand for the Tanjung chili is small, the farmers plant it as the demand is constant; hence the revenue can be counted on for life.…”
Section: The Op Chili Farmers' Preference Rate Analysis To Tanjung Ca...mentioning
confidence: 99%
“…There are two kinds of chili seed distributed in Indonesia, hybrid and open-pollinated (OP) (Kusmanto et al, 2015). Farmers use hybrid chili because it produces high yield (Herison et al, 2014). However, farmers should buy seeds for each planting season, which is costly for them (Ferniah et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Researches on chilli especially those in Bengkulu area of Indonesia have been performed such as chilli genetic improvements (Ganefianti, 2000;Ganefianti and Fahrurrozi, 2018;Herison et al, 2014), and chilli production technologies (Handajaningsih et al, 2015). Most experiment aspects on production technology are related to the strategy in reducing input of synthetic fertilizers as well as synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%